An investigation into understanding of academic literacies of students registered in Early Childhood Development courses - Hackmack, Karin Erna (Rhodes University, Faculty of Education, Department of Education, 2014)
Purpose and research questions- This research was based on students enrolled on courses at Rhodes University's Centre for Social Development, an Institute delivering Early Childhood Development courses in the Grahamstown area. Having provided the students with access to a career path and its courses, it was imperative to assist the students to develop a standard of academic literacy comparable to that of in-service education students, in the Intermediate and Senior Phases. This study was influenced by Gee's (2004) definition of literacy as 'mastery over a discourse'. Gee (1990) termed discourse as the socially accepted way of thinking, believing and being. The study therefore investigated the enablers which assisted students to produce academic texts. This was achieved by finding out how the students and the course facilitators construct academic literacy; in other words what their discourses were regarding academic literacy. In order to ascertain this information, the students and the course facilitators were asked what reading and writing the students had done prior to enrolling on the course, what they had brought to the course, what the students and the course facilitators thought comprised a successful academic assignment, and how the students were supported in their academic literacy during the course. Data was gathered through interviews with both students and course facilitators, analysis of course assignments, and assessment reports written by the course facilitators. This data was analysed, looking for discourses on similarities and contradictions. Critical Discourse analysis was used to investigate the discourses that the course facilitators and students were using. Findings: It was evident from the data that the autonomous view of literacy was predominantly used. The course facilitators and, to a limited extent, the students, saw literacy as a set of technical skills that needed to be mastered. The students and course facilitators did not take into account that literacy is a social practice, and that literacy occurs within a particular social context and cultural context. The course facilitators tended to hold a deficit discourse related to the perception of inferior education under Bantu Education, which was seen as an inhibiting factor to academic literacy and academic success. The discourse of second language was also an issue that both the course facilitators and the students noted which prevented students' academic literacy. Christie's (1985) Received Tradition of Literacy, which focused on the forms and functions of literacy, was a discourse that both the students and the course facilitators ascribed to. Conclusions and recommendations: The course facilitators' and students' discourses were very similar, both being embedded within the autonomous and deficit models of literacy. It is recommended that course facilitators become cognisant with the models of academic literacy and that they become aware of the various discourses evident on the course and articulate these discourses for themselves. Furthermore they should assist the students by clearly articulating and unpacking the course requirements regarding academic literary.
Keywords: Academic writing -- Study and teaching -- South Africa -- Grahamstown; Discourse analysis; Information literacy -- Study and teaching (Higher); Information literacy -- Social aspects; Early childhood education -- Study and teaching (Higher) -- South Africa -- Grahamstown; Education -- Study and teaching (Higher) -- South Africa -- Grahamstown